Anticoagulation and Antiplatelet Agents in Peripheral Arterial Interventions - Taylor, Jordan; Stiepel, Henry R., III; Keefe, Nicole (Seminars in Interventional Radiology, 2022)
Effective revascularization of peripheral artery disease relies on periprocedural pharmacological regulation of the clotting cascade. Patient-specific factors such as cardiovascular risk factors, contraindications, and individual psychosocial factors must be considered when initiating post revascularization management. Management with anticoagulant and antiplatelet agents is discussed to guide the interventionalist on which therapy may be appropriate for their patient. While exact treatment may be institution and provider dependent, the interventionist must be familiar with the available classes of medications and how they can be prescribed in the postprocedural setting to improve cardiovascular outcomes.
Keywords: anticoagulant; antiplatelet; peripheral artery disease; dual-antiplatelet therapy; interventional radiology